A novel RPL-based multicast routing mechanism for wireless sensor networks. (24th February 2020) - Hwang, Ren-Hung; Peng, Min-Chun; Wu, Cheng-Yu; Abimannan, Satheesh
The IPv6 routing protocol for low-power and lossy networks (RPL) provides the multipoint-to-point, point-to-multipoint, and point-to-point routing mechanisms for wireless sensor networks. However, for point-to-multipoint, i.e., multicast from the sink node, the RPL poses only the principles of routing operation, and the practical mechanism is still an open issue. In this paper, we propose a wireless shortest path heuristic (W-SPH) mechanism for constructing a multicast tree which builds effective routing topology for multicast traffic, and as a consequence, yields higher energy efficiency. We also introduce the proactive multicast forwarding with RPL (PMFR), a multicast mechanism with proactive retransmission and early relay, to increase the reliability of the multicast. Our simulation results demonstrate that the PMFR can achieve a significantly higher delivery ratio and a 50% lower delay than previous works. The PMFR also reduces about 40% energy consumption as compared to the multicast protocol for low-power and lossy networks (MPL).